THE ERRORS IN SOLVING GEOMETRY QUESTIONS ON CONGRUENCE AND SIMILARITY TOPICS BY FLORENCE LITTAUER MIXED PERSONALITY TYPE STUDENTS - Hariyanto, Nanang Hadi; Purwanto, Purwanto; Kusumasari, Vita (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2025)
This research aims to describe errors and determine the factors that cause errors in solving geometry problems in terms of students' mixed Florence Littauer personality types. This research is qualitative descriptive research. The subjects of this research were ninth-grade students at SMPN 13 Malang who had been given material on "similarity and congruence of triangles". Data collection techniques include questionnaires, test questions, interviews. Data analysis techniques in this research include data reduction, data presentation, and drawing conclusions. The validity of the data uses triangulation techniques through the results of test questions and interviews. The results of the research can be concluded that students with mixed natural personality types (SCA) make five errors, namely reading errors, understanding errors, transformation errors, process skills errors, and errors in writing the final answer. Students with mixed-complementary personality types (SCP) have one error, namely an error in writing the final answer. Students with the opposite personality type (SCL) experienced two errors in answering geometry questions, namely transformation errors and process skill errors. The factors that cause errors are (a) not being able to understand the geometry material well, (b) being weak in the prerequisite material, and (c) carelessness made by students when solving geometry problems.